2005
DOI: 10.1007/s11199-005-6764-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Psychological Distress in Taiwanese Secondary School Boys and Girls

Abstract: This study was designed to investigate predictors of psychological distress in secondary school boys (n =779) and girls (n = 893) in Taiwan. Participants completed anxiety and depression scales as part of a larger study. Gender, GPA, parenting practices, self-esteem, and personality/satisfaction were significantly correlated with psychological distress. Significant gender differences were found in students' psychological distress, GPA, stereotyped thinking, academic self-expectations, parental expectations, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Situated in a society holding both values, Taiwanese women are struggling to form a clear adult identity due to conflicting gender-role expectations. For example, in a study examining predictors of Taiwanese high school students' psychological distress (i.e., depression and anxiety; Hong et al 2005), girls' distress levels are shown to be affected by multiple predictors (e.g., GPA, parenting practice, selfesteem) whereas boys' stress is only related to their current self-esteem. That is, girls perceive multiple sources of stress in their environment that appear to be related to mixed messages about their expected role.…”
Section: Gender-role Expectations and Women's Identity Development Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Situated in a society holding both values, Taiwanese women are struggling to form a clear adult identity due to conflicting gender-role expectations. For example, in a study examining predictors of Taiwanese high school students' psychological distress (i.e., depression and anxiety; Hong et al 2005), girls' distress levels are shown to be affected by multiple predictors (e.g., GPA, parenting practice, selfesteem) whereas boys' stress is only related to their current self-esteem. That is, girls perceive multiple sources of stress in their environment that appear to be related to mixed messages about their expected role.…”
Section: Gender-role Expectations and Women's Identity Development Inmentioning
confidence: 99%
“…Taiwanese women face a dilemma when forming an adult identity. Their emergent liberal gender beliefs and personal aspirations (Chia et al 1994;Tian 2011) contradict traditional Confucian values regarding gender-role expectations that encourage them to conform to authority and show a strong commitment only to marriage and family (Cheng 2004;Hong et al 2005;Lee 2009). They must attempt to maintain well-being in the face of this challenge.…”
Section: Gender-role Expectations and Women's Identity Development Inmentioning
confidence: 99%
See 3 more Smart Citations